2011
DOI: 10.1177/039463201102400315
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Diagnostic Score for the Diagnosis of Autoinflammatory Diseases in Adults

Abstract: The first two authors contributed equally to this study Most autoinflammatory disorders typically come out in the pediatric population, although a limited number of patients may experience disease onset during adulthood. To date, a late disease onset has been described only in familial Mediterranean fever, caused by mutations in the MEFV gene, and in tumor necrosis factor receptor-associated periodic syndrome, caused by mutations in the TNFRSFIA gene. The relative rarity and lack of information on adult-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…Mean age at disease onset is around 3 years. Nevertheless TRAPS is the most variable and multiform entity amongst autoinflammatory diseases both in terms of age at disease onset and clinical manifestations [2][4], [9]. This heterogeneity is probably related to the wide spectrum of known TNFRSF1A mutations [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age at disease onset is around 3 years. Nevertheless TRAPS is the most variable and multiform entity amongst autoinflammatory diseases both in terms of age at disease onset and clinical manifestations [2][4], [9]. This heterogeneity is probably related to the wide spectrum of known TNFRSF1A mutations [10].…”
Section: Introductionmentioning
confidence: 99%
“…These subjects also have a greater risk of developing AA amyloidosis, the most troublesome TRAPS complication [2], [3], [12]. On the contrary low-penetrance variants seem to be associated with a milder phenotype, a later disease onset and a lower risk of amyloidosis [3][9], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although pediatric onset is considered the norm, the presence of low-penetrance mutations in the MEFV and TNFRSF1A genes may be identified in adulthood [69][70][71][72] as adult subjects carrying low-penetrance alleles and characterized by a late disease onset display as a less aggressive phenotype [73]. Nonetheless, FMF is the most common recessive and TRAPS the most common dominant autosomally inherited autoinflammatory disorder.…”
Section: The Autoinflammatory Side Of Irapmentioning
confidence: 99%
“…In order to improve genetic diagnosis in adults suspected to have AIDs, Cantarini et al have identified some variables strongly related to the probability of detecting mutations in the TNFRSF1A gene and also in the MEFV gene (which is responsible for familial Mediterranean fever). In addition, they developed, validated, and revised a diagnostic score for identifying patients at high risk to carry these mutations according to clinical manifestations, age of disease onset, and family history [55, 84,85]. However, before this score can be recommended for widespread application, further evaluation by means of longitudinal studies on populations from different geographical areas is required.…”
Section: Traps Clinical Featuresmentioning
confidence: 99%